Interstitial Fibrosis as a Common Counterpart of Histopathological Risk Factors in Papillary Thyroid Microcarcinoma: A Retrospective Analysis - Sahin, Can; Inan, Mehmet Arda; Bilezikci, Banu; Bostanci, Hasan; Taneri, Ferit; Kozan, Ramazan (Diagnostics (Basel), 2024)
Purpose. Interstitial fibrosis in papillary thyroid microcarcinoma is a subject which is under-investigated. The aim of this study is to determine the relationship between interstitial fibrosis, the subtypes of papillary microcarcinoma, and the established prognostic factors. Material and Methods. A total of 75 patients diagnosed with papillary microcarcinoma of the thyroid from January 2011 to December 2020 have been evaluated retrospectively, using demographic features, tumor size, subtype of the tumor, surgical margin status, unifocality, lymphovascular invasion, extracapsular spread and lymph node metastasis as parameters. Hematoxylin and eosin slides were reviewed for interstitial fibrosis. Results. The study includes 13 males and 62 females, in a total of 75 patients. There were 51 patients (68%) with interstitial fibrosis and 24 (32%) patients without interstitial fibrosis. Among them, 45 (60%) were classic, 27 (36%) were follicular variant and 3 (4%) were other subtypes. Interstitial fibrosis is significantly associated with bilaterality (p = 0.023), multifocality (p = 0.004), capsule invasion (p < 0.001) and lymph node metastasis (p = 0.043). Evaluation of tumor sub groups showed significant increased risk of lymphovascular invasion in the follicular variant (p = 0.019). Conclusion. Although the relationship of interstitial fibrosis and prognosis of other cancer types has been discussed, there are few studies in the literature regarding its effect on the prognosis of papillary microcarcinoma. Our results show that interstitial fibrosis can be used as a risk factor. However, new studies are needed to clearly reveal the physiopathology of interstitial fibrosis and its effect on tumorigenesis.